A stem group echinoderm from the basal Cambrian of China and the origins of Ambulacraria - Timothy P. Topper (Nature Portfolio, 2019)
The early evolution of the deuterostomes is not well resolved. Here, Topper and colleagues investigate the early Cambrian metazoan Yanjiahella biscarpa, concluding that it is a stem echinoderm, is among the oldest known deuterstomes, and supports an ancestral enteropneust body plan in hemichordates.